The Future of UK Services Trade Post-Brexit: Unlikely to Be Bright - Olga Pindyuk (The Vienna Institute for International Economic Studies (wiiw), 2019)
Trade in services was overshadowed by trade in goods in the Brexit debate, undeservingly so as services account for almost half of the UK cross-border exports and the EU is a major market for UK services exporters. Leaving the EU Single Market in services will cause increased regulatory costs of trading services and could have significant effects on the volume and composition of UK services exports under any exit deal. The highest rise in trade costs is to be expected in professional services, such as legal services, architecture, engineering, and accounting. With a rise in cross-border trade barriers there would be a relative increase in the proportion of services provided via a more costly physical presence within the EU. Regulatory heterogeneity among the EU members towards third countries will be an additional factor behind significant shifts in the sectoral and geographic composition of the UK services exports.
Keywords: L80; F13; F15; 330; services trade; Brexit; Single Market